2020
DOI: 10.1108/arla-04-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Influence of support on work engagement in nursing staff: the mediating role of possibilities for professional development

Abstract: PurposeThe purpose of this study is to examine the effects of colleague and supervisor support on work engagement, examining the mediating role of possibilities for professional development in a healthcare setting.Design/methodology/approachA cross-sectional survey design was used. A sample of 253 Colombian nurses from a private hospital completed a series of questionnaires.FindingsAccording to the results, support from both colleagues and supervisors influences the work engagement of healthcare personnel. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 74 publications
2
26
0
1
Order By: Relevance
“…The findings of the study indicate that supervisor support has a significant impact on teacher work engagement. These findings are in line with the study conducted by Contreras, Abid, Govers and Elahi (2020) who stated that supervisor support has a significant relationship with work engagement. This is because the support of the supervisor is able to increase work engagement through the existence of a harmonious relationship between the two parties, namely the supervisor and the employees.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the study indicate that supervisor support has a significant impact on teacher work engagement. These findings are in line with the study conducted by Contreras, Abid, Govers and Elahi (2020) who stated that supervisor support has a significant relationship with work engagement. This is because the support of the supervisor is able to increase work engagement through the existence of a harmonious relationship between the two parties, namely the supervisor and the employees.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with the statement by Park, Hye-Seung and Eun-Jee (2018) who stated that organizations can provide more professional training and development opportunities to meet the needs of employees if they get support and information from supervisors. The study conducted by Contreras, Abid, Govers and Elahi (2020) has supported the findings of the study of Ahmed, Ahmad and Jaaffar (2017); Mohamed and Ali (2016) which showed that supervisor support has a positive impact on work engagement. The findings of the study revealed that employees who have a harmonious relationship with supervisors will be motivated to perform and engage with tasks in the workplace (Shahid, Amdan, Alwi, Azmi & Hassan, 2016).…”
Section: Review Of Literaturesupporting
confidence: 79%
“…The results show a supplementary fit (Leroy et al, 2018) between AMO HRM practices and service leadership, whereby service leaders play a pivotal role in HRM practices helping to implement AMO HRM practices more effectively (Nishii and Paluch, 2018). Prior studies in healthcare confirmed that HRM practices or leadership styles providing support to employees, and taken in isolation, increase job satisfaction (Farrington and Lillah, 2019) and engagement (Contreras et al, 2020;Shantz et al, 2016). However, literature leaves room to: (1) explore the joint effect of HRM practices and leadership on positive attitudes, and (2) explore this joint effect on a wider conceptualization of work-related well-being, involving engagement, trust, and exhaustion.…”
Section: Discussionmentioning
confidence: 74%
“…Recent empirical study found that the perception of organizational support, thriving at work, employee calling and flourishing positively enhances work engagement [46,47]. Another study found that colleague support, supervisor support, and possibilities for professional development boost work engagement of employees [48]. Furthermore, it is identified that employees are most probably engaged with the work when they are thriving, prosocially motivated in civil environment [49].…”
Section: Family Motivation and Work Engagementmentioning
confidence: 99%